2021
DOI: 10.32920/14637144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoscale and Macroscale Scaffolds with Controlled-Release Polymeric Systems for Dental Craniomaxillofacial Tissue Engineering.

Abstract: Tremendous progress in stem cell biology has resulted in a major current focus on effective modalities to promote directed cellular behavior for clinical therapy. The fundamental principles of tissue engineering are aimed at providing soluble and insoluble biological cues to promote these directed biological responses. Better understanding of extracellular matrix functions is ensuring optimal adhesive substrates to promote cell mobility and a suitable physical niche to direct stem cell responses. Further, appr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…The fibers can be loaded with various biological payloads like drugs, dyes, enzymes and proteins as nanoparticles, nanowires and molecular species (usually termed as payload carriers) for different applications [92], [98], [102], [109], [161]. Hong et al [109] showed the feasibility of protein (BSA-Bovine serum albumin) adsorption on porous silicate fibers with small pore fibers (3.8 nm pore size) showing slow BSA adsorption reaching equilibrium at 65 mg/g after 40 min, while large pore fibers (40 nm pore size) showing high BSA adsorption attaining equilibrium capacity of 130 mg/g after 40 min.…”
Section: Functional Fibersmentioning
confidence: 99%
“…The fibers can be loaded with various biological payloads like drugs, dyes, enzymes and proteins as nanoparticles, nanowires and molecular species (usually termed as payload carriers) for different applications [92], [98], [102], [109], [161]. Hong et al [109] showed the feasibility of protein (BSA-Bovine serum albumin) adsorption on porous silicate fibers with small pore fibers (3.8 nm pore size) showing slow BSA adsorption reaching equilibrium at 65 mg/g after 40 min, while large pore fibers (40 nm pore size) showing high BSA adsorption attaining equilibrium capacity of 130 mg/g after 40 min.…”
Section: Functional Fibersmentioning
confidence: 99%